Implikasi Perceraian di Bawah Tangan Terhadap Hak Nafkah Istri dan Anak Perspektif Hukum Islam dan Hukum Positif (Studi Kasus di Desa Orodalam Kecamatan Camplong Kabupaten Sampang) - Holil Holil; Urwatul Wusqa (Indo-MathEdu Intellectuals Journal, 2026)
The phenomenon of underhand divorce is still common in Orodalam Village, even though the practice is not in accordance with applicable Indonesian law. This study aims to analyze the implications of underhand divorce on the fulfillment of the wife's and children's rights to maintenance, viewed from the perspective of Islamic law and positive law. This study uses a qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, and its validity was tested through extended observation and triangulation. The results show that underhand divorce is still often practiced because it is considered easier and cheaper, and is influenced by the low legal understanding of the community. From an Islamic legal perspective, underhand divorce is considered religiously valid if it meets the requirements and pillars of divorce, but has a negative impact on the fulfillment of the wife's and children's rights to maintenance. Meanwhile, from a positive legal perspective, such divorce has no legal force because it is not conducted through a Religious Court, thus complicating the enforcement of maintenance rights. This research is expected to provide academic contributions and become a consideration for the community and further research.